Caregiver perspectives and preferences for acute otitis media management - Holly M. Frost; Amy Keith; Thresia Sebastian; Timothy C. Jenkins (Cambridge University Press, 2021)
Surveyed caregivers of children in Denver, Colorado, with acute otitis media (AOM) preferred immediate antibiotics over delayed antibiotics or observation. Overall, 77% stated that they would immediately fill a prescription written as delayed. In contrast, 86% of caregivers favored whichever duration was recommended by the provider or the shortest duration necessary.